Pathological and molecular findings of avian avulavirus type 1 outbreak in pigeons (Columba livia) of southern Brazil - Suyene O. Souza; Gabriela Fredo; Priscilla M. Dupont; Ronaldo V. Leite-Filho; Jens P. Teifke; Saulo P. Pavarini; Cláudio W. Canal; David Driemeier (Pesquisa Veterinária Brasileira)
ABSTRACT: The Newcastle disease, caused by avian avulavirus type 1 strains (APMV-1) is an important avian disease involved into high rates of mortality and economic losses. Several outbreaks have been reported over the last 30 years in Columbiformes in different parts of the world, caused by a adapted variant strain of AAvV-1, called pigeon paramyxovirus type 1 (PPMV-1). A high mortality associated with an outbreak was analyzed in free-living pigeons (Columba livia) in a public square in Porto Alegre in Southern Brazil. A total of 24 pigeons moribund or freshly dead, within five weeks interval were submitted to necropsy, histopathological, immunohistochemical (anti-Newcastle), and RT-PCR followed by sequencing of the amplification products analysis. They presented neurological signs, non-suppurative encephalitis and encephalomyelitis, and mononuclear inflammatory infiltrate in different organs. Immunohistochemical analysis in nine pigeons tissue showed that anti-Newcastle was expressed in brain, kidney, liver and pancreas. The RT-PCR test for the M protein of Newcastle disease virus was positive in six pigeons. The differential diagnosis of Influenza, West Nile, Mycoplasma gallisepticum and Mycoplasma synoviae in all pigeons presented negative results. The sequence of amino acids in the cleavage site region of the F protein was 112RRQKRF117 classifying the strain as virulent. The phylogenetic analysis classified this virus strain into Class II and VI genotype.